The The Silent Classroom Phenomenon: An Analysis of Generation Z's Nonverbal Communication in the Learning Process: Fenomena Silent Classroom: Analisis Komunikasi Nonverbal Generasi Z Dalam Proses Pembelajaran - Salman Al Farizi; Iwan Djoko Prasetyo; Redi Panuju (LPPM Stikosa - AWS, 2025)
The phenomenon of silent classroom has become a significant challenge in the world of education, especially for Generation Z students who have different communication characteristics from previous generations. This qualitative research was conducted at SMK Negeri 1 Kamal Bangkalan by involving 64 students and 31 teachers as research subjects. Data collection was conducted through participatory observation and in-depth interviews to identify nonverbal communication patterns that emerged when students tended to be verbally passive. The results of the study show that students' silence is not an indication of involvement, but a shift in the form of communication from verbal to nonverbal which is manifested through facial expressions, body gestures, eye contact, and the use of digital media. The dominant factors that cause verbal passivity include fear of being wrong, feelings of embarrassment, lack of confidence, and a preference for digital communication that is characteristic of Generation Z. Research found that 75% of students experience a fear of making mistakes, while 59.4% are more comfortable expressing themselves through digital symbols. Although 90.3% of teachers admitted to paying attention to nonverbal communication, 58% had experienced misunderstandings in interpretation. Learning strategies that integrate technology, gamification, and creating a supportive psychological environment have proven effective in increasing student participation by up to 79.7%. This study concludes that understanding of nonverbal communication of Generation Z is the key to learning effectiveness in the digital era.